2021
DOI: 10.3389/fendo.2021.641623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Day 3 and Day 5/6 Embryo Quality on the Reproductive Outcomes in the Single Vitrified Embryo Transfer Cycles

Abstract: ObjectiveTo explore the live birth rate and neonatal outcome after single vitrified blastocyst transfer versus single vitrified cleavage-stage embryo transfer at different grades of embryo quality.MethodsA retrospective cohort study including 6077 single vitrified-thawed embryo transfer cycles was performed in the time-period from January 2013 to December 2018.ResultsAfter controlling for potential confounding variables, there are 161% increased odds of a live birth after transfer of single good quality embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…However, it has been shown that frozen embryo transfer on day five was associated with a lower birthweight compared to frozen embryo transfer on day three (De Vos et al, 2018). On the contrary, another study with large samples has shown that there was a significantly higher birth weight after good-quality blastocyst transfer on day five or day six compared to day-3 embryo transfers (Wang et al, 2021). Multiple births are the complication associated with multiple embryos transferred, associated with adverse health outcomes, including low birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been shown that frozen embryo transfer on day five was associated with a lower birthweight compared to frozen embryo transfer on day three (De Vos et al, 2018). On the contrary, another study with large samples has shown that there was a significantly higher birth weight after good-quality blastocyst transfer on day five or day six compared to day-3 embryo transfers (Wang et al, 2021). Multiple births are the complication associated with multiple embryos transferred, associated with adverse health outcomes, including low birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…Existing data on the effect of culture duration on neonatal birth weight are conflicting. Some studies have reported that compared with cleavage embryos, blastocyst transfer tends to have a higher mean birth weight and an increased proportion of LGA ( 9 , 10 , 28 ). An animal study has demonstrated that the effects of delayed blastulation and extended culture on blastocysts can be cumulative ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have indicated that frozen embryo transfer (FET) is associated with a higher birthweight and an increased risk of delivering LGA babies as compared to fresh embryo transfer ( 7 , 8 ), implying that the process of cryopreservation can adversely affect the embryo quality and developmental potential. Moreover, FET at the blastocyst stage is associated with higher birthweight and an increased risk of LGA compared with the cleavage stage ( 9 , 10 ). However, limited studies have compared the perinatal outcomes after the transfer of frozen-thawed blastocysts formed on D5 and D6, and the results remain controversial ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the ART outcome, several meta-analyses suggested a negative association between female obesity and live birth rates [ 5 7 ], while no adverse effects of obesity on pregnancy or live birth outcome have been reported in others [ 8 , 9 ]. Although embryo quality largely determines the success of implantation and live birth [ 10 ], Herbemont et al [ 11 ] indicated that poor or good embryo quality at days 2 and 3 were not predictive of the implantation of good-quality blastocysts. On the other hand, an increase in live birth rate was associated with blastocyst transfer on day 5 when compared with embryo transfer on day 3 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although embryo quality largely determines the success of implantation and live birth [ 10 ], Herbemont et al [ 11 ] indicated that poor or good embryo quality at days 2 and 3 were not predictive of the implantation of good-quality blastocysts. On the other hand, an increase in live birth rate was associated with blastocyst transfer on day 5 when compared with embryo transfer on day 3 [ 10 ]. Interestingly, the study by Blank et al [ 12 ] revealed that pregnancy outcome could be enhanced when transferring an embryo that has an improvement in quality between days 3 and 5 as opposed to one that has remained stable.…”
Section: Introductionmentioning
confidence: 99%